Maintenance of Cell Fate by the Polycomb Group Gene Sex Combs Extra Enables a Partial Epithelial Mesenchymal Transition in Drosophila. Issue 12 (1st December 2020) - Jefferies, Grace; Somers, Jason; Lohrey, Isabelle; Chaturvedi, Vishal; Calabria, Jacob; Marshall, Owen J; Southall, Tony D; Saint, Robert; Murray, Michael J
Abstract: Epigenetic silencing by Polycomb group (PcG) complexes can promote epithelial-mesenchymal transition (EMT) and stemness and is associated with malignancy of solid cancers. Here we report a role for Drosophila PcG repression in a partial EMT event that occurs during wing disc eversion, an early event during metamorphosis. In a screen for genes required for eversion we identified the PcG genes S ex combs extra ( Sce ) and S ex combs midleg ( Scm ) . Depletion of Sce or Scm resulted in internalized wings and thoracic clefts, and loss of Sce inhibited the EMT of the peripodial epithelium and basement membrane breakdown, ex vivo. Targeted DamID (TaDa) using Dam-Pol II showed that Sce knockdown caused a genomic transcriptional response consistent with a shift toward a more stable epithelial fate. Surprisingly only 17 genes were significantly upregulated in Sce -depleted cells, including Abd-B, abd-A, caudal, and nub bin . Each of these loci were enriched for Dam-Pc binding. Of the four genes, only Abd-B was robustly upregulated in cells lacking Sce expression. RNAi knockdown of all four genes could partly suppress the Sce RNAi eversion phenotype, though Abd-B had the strongest effect. Our results suggest that in the absence of continued PcG repression peripodial cells express genes such as Abd-B, which promote epithelial state and thereby disrupt eversion. Our results emphasize the important role that PcG suppression can play in maintaining cell states required for morphogenetic events throughout development and suggest that PcG repression of Hox genes may affect epithelial traits that could contribute to metastasis.